The role of mass media as a channel to learn about Islam among muslims in Gombak - Abdul Manan, Kamaruzzaman; Abdul Jalil, Mohd Noh; al-Akiti, Muhammad Ayman; Borhan, Lihanna; Alias, Majdan; Abdul Rahman, Shukran; Ismail, Khamsiah (International Islamic University Malaysia, 2022)
Mass media’s evolution today requires the dāʿiy to equip themselves with communication skills as part of da’wah. This is because the mass media offers borderless and limitless Islamic contents platform that can reach many Muslim in 24/7. However, mass media also has disadvantages where fake preacher and extremist can freely promote their ideologies. Moreover, past literature on the mass media focusses more on the development of Islamic content yet very few studied on the importance of its channel of distribution for da’wah. This study focusses on mass media’s role in educating and analyse its favourability as a tool for Islamic learning. The respondents were 596 Muslims in Gombak. The results highlight the practicality, importance, and opportunities of mass media to propagate a better understanding of Islam that can be utilised by the government and religious authorities in formulating policies and strategies for teaching Islam more effectively.